Mesoporous niobium-doped titanium dioxide films from the assembly of crystalline nanoparticles: study on the relationship between the band structure, conductivity and charge storage mechanism. Issue 5 (24th November 2016) - Yue, Junpei; Suchomski, Christian; Voepel, Pascal; Ellinghaus, Ruediger; Rohnke, Marcus; Leichtweiss, Thomas; Elm, Matthias T.; Smarsly, Bernd M.
Abstract : The pseudocapacitive contribution to Li storage in metal oxides was studied on mesoporous films of Nb-doped TiO2 . Abstract : The charge storage mechanism of nanostructured intercalation materials such as anatase (TiO2 ) is still a matter of intense research, because it provides the basis for designing electrochemical energy storage and conversion materials. In this work, we addressed the relationship between conductivity and the charge storage mechanism exemplified with nanostructured Nb-doped TiO2 . Nanoparticles of Nb-doped TiO2 were prepared by a novel two-step solvothermal process based on tert -amyl alcohol as the solvent. Several state-of-the-art techniques, including X-ray diffraction along with Rietveld refinement and Raman and X-ray photoelectron spectroscopy, were used to analyze the phase composition, the chemical oxidation state and the structure after doping with different niobium contents. Mesoporous Nb-doped TiO2 films with uniform pore sizes of 15 to 18 nm were produced by dip-coating employing these nanoparticles as building blocks. It is found that 5 at% Nb-doped TiO2 exhibits the highest conductivity. The analysis of the peak currents in the cyclic voltammetry of the mesoporous films indicates that the pseudocapacitive current contribution varies with the conductivity in the same trend. This correlation can be described qualitatively by the changes in the space charge layer at the interface with varying carrier concentration. Such a finding implies that doping not only affects the charge storage in the bulk due to changes of kinetic parameters including the chemical diffusion coefficient and electronic conductivity, but also influences the surface-related storage mechanism of a given nanostructured material. These results further provide a valuable insight in searching for and designing materials applied in pseudocapacitors.